IMPLEMENTATION OF ORGANIZATIONAL CULTURE ON VILLAGE OWNED ENTERPRISES (BUMDes) VILLAGE KARANGPAPAK CISOLOK SUBDISTRICT SUKABUMI DISTRICT - Faizal Mulia Z Faizal Mulia Z (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
Village Owned Enterprises (BUMDes) is one of the business units managed by the village community as the spearhead of the welfare of the village community in the field of micro economics, the background of this research is due to almost every village, especially in Karangpapak Village, Cisolok Subdistrict, District Sukabumi, the organizational culture has not yet run both of these are seen in the management of BUMDes which when formed did not provide good performance and was not in accordance with Permendesa Number 4 of 2015 concerning Establishment, Management and Management, and Disbanding of Village-Owned Enterprises, the expected outcome of this research was the creation of the Karangpapak BUMDes Organizational Culture in accordance with what is expected by the village government and in accordance with existing regulations that serve as guidelines for regions and villages in the formation and management of BUMDes, the research method to be conducted is qualitative descriptive based on primary and secondary data consisting of 3 In forman namely Head Of Village, Director of BUMDes and Community Elements. Keywords: Organizational Culture, BUMDes